Bio fuel production from crude Jatropha oil; addition effect of formic acid as an in-situ hydrogen source. (15th June 2016) - Hwang, Kyung-Ran; Choi, Il-Ho; Choi, Hye-Young; Han, Jeong-Sik; Lee, Kyong-Hwan; Lee, Jin-Suk
Highlights: Deoxygenation reaction of crude Jatropha oil was carried out to produce oxy-free hydrocarbons. Hydrocarbon was main product, about 97%, in the liquid product and deoxygenation degree was about 99.5%. Addition of formic acid as hydrogen donor is favorable deoxygenation reaction of oil and initial deactivation of catalyst. Abstract: The catalytic deoxygenation reaction of crude Jatropha oil (CJO) was carried out to produce oxy-free hydrocarbons in assistance with hydrogen in-situ produced from formic acid solution (30%) and addition effect of formic acid was discussed on the deoxygenation reaction and product distribution. Mixing of formic acid with reactant yielded higher oil conversion and higher selectivity to normal hydrocarbon (mainly C15 and C17 ) than those of the other cases (no mixing or water addition). Total surface area and total pore volume of used catalysts in the batch reactor followed the order Pd/C–formic acid solution > Pd/C–water > Pd/C–no co-reactant under constant conditions. Moreover, significantly higher degree of deoxygenation with a high initial resistance to catalyst deactivation was observed on Pd/C catalyst in the presence of formic acid during the continuous catalytic reaction. This means that addition of formic acid solution as the hydrogen donor is favorable the deoxygenation reaction and the initial deactivation of catalyst. As results of continuous deoxygenation reaction using the mixture of oil and formic acid, normal hydrocarbon in the liquid product was main product, about 97%, and the degree of deoxygenation was about 99.5%.